Management model of the Trang Provincial Sports Association (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today's sports associations need to develop their management approach and pays attention to the qualitydevelopment of athletes to be in line with developmentof The National Development Plan. Therefore, the management of theassociation is necessary to have knowledge, understanding, curiosity and systematic development of the association in relationto management approaches aimed at developing athletes and having higher potential.The main objectives wereto studycomponents of the management model of Trang Provincial Sport Association and to develop the management model of TrangProvincial Sports Association. The survey method was used and divided into three parts (i) In-depth interviews from 5 expertsby purposive random sampling (ii) Delphi technique, the sample group in the research was obtained by a method of purposiverandom sampling of 18 people as follows: (1) Two representatives from the sports policy management group of Thailand (2)Five groups of the experts were consisted of one representative of the executive director at the policy level of the Tourism andSport Department, three representatives those who were the executive committee from sport associations, two representativesthose who were the secretary, or the sport club president, four representatives those who experts in administration, and sixrepresentatives those who were the stakeholders. (iii) Focus Group was obtained by purposive random sampling all total 9people those who were examined for suitability and feasibility of implementation with three persons of the club's executivecommittee, three persons of the club secretary, three persons of the sports professionals or athletic trainers. The investigatorsfound that the management model of the Trang Provincial Sports Association, the study was able to synthesize themanagement components of the Trang Provincial Sports Association which can be divided into 9 areas: 1. Trainers 2. SportsScience 3. Sport facility 4. Budget 5. Organization Management 6. Training 7. Recruiting 8. Performance 9. Supporting.